2022
DOI: 10.1038/s41467-022-34202-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signatures associated with maintenance of genome stability and venom turnover in two parasitoid wasps

Abstract: Parasitoid wasps are rapidly developing as a model for evolutionary biology. Here we present chromosomal genomes of two Anastatus wasps, A. japonicus and A. fulloi, and leverage these genomes to study two fundamental questions—genome size evolution and venom evolution. Anastatus shows a much larger genome than is known among other wasps, with unexpectedly recent bursts of LTR retrotransposons. Importantly, several genomic innovations, including Piwi gene family expansion, ubiquitous Piwi expression profiles, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 97 publications
0
32
0
Order By: Relevance
“…A total of·2,126 strictly single-copy orthologous genes among ten Pyraloidea insects were used for identification of rapidly evolving genes and positively selected genes. We used Codeml in PAML v4.9 ( Yang, 2007 ) to detect rapidly evolving and positive selection signals on the E. elutella branch as we described previously ( Yang et al, 2021 ; Ye et al, 2022 ). Briefly, we used the branch model in Codeml to detect rapidly evolving genes on the E. elutella branch, and a likelihood ratio test (LRT) was performed compare the null model (assuming that all branches have evolved at the same rate) and the alternative model ( E. elutella branch has a different evolutionary rate).…”
Section: Methodsmentioning
confidence: 99%
“…A total of·2,126 strictly single-copy orthologous genes among ten Pyraloidea insects were used for identification of rapidly evolving genes and positively selected genes. We used Codeml in PAML v4.9 ( Yang, 2007 ) to detect rapidly evolving and positive selection signals on the E. elutella branch as we described previously ( Yang et al, 2021 ; Ye et al, 2022 ). Briefly, we used the branch model in Codeml to detect rapidly evolving genes on the E. elutella branch, and a likelihood ratio test (LRT) was performed compare the null model (assuming that all branches have evolved at the same rate) and the alternative model ( E. elutella branch has a different evolutionary rate).…”
Section: Methodsmentioning
confidence: 99%
“…The highly dynamic evolution of OR genes, which discriminate odour molecules derived from hosts and host habitats, is crucial for parasitoids to locate different hosts 17 19 . Additionally, venom proteins, which regulate host immunity, development and metabolism, likely evolve quickly and adopt novel functions in response to different host species 15 , 16 , 20 . Although the biology of T. elegans has been studied, little genetic information is presently available, which constrains its desirability and application as a biocontrol agent.…”
Section: Background and Summarymentioning
confidence: 99%
“…In particular, Peng et al (2020) reported that Anastatus fulloi Sheng and Wang (Hymenoptera: Eupelmidae) appears to have been consistently misidentified as A. japonicus in mainland China; the extensive biological literature published under A. japonicus in China has thus been called into question [ 1 ]. Lately, Ye et al identified that 104 ORs in the genome of A. japonicus had a highly duplicated 9-exon subfamily but did not analyze the expression profiles of ORs and other olfactory genes [ 40 ].…”
Section: Introductionmentioning
confidence: 99%